Biological control of potato common scab and growth promotion of potato by Bacillus velezensis Y6 - Tao, Huan; Wang, Shisong; Li, Xiaoyu; Li, Xiaobo; Cai, Jianying; Zhao, Lanfeng; Wang, Jia; Zeng, Ji; Qin, Yuzhi; Xiong, Xingyao; Cai, Yanfei (Frontiers in Microbiology, 2023)
Potato common scab, caused mainly by Streptomyces scabies, causes surface necrosis and reduces the economic value of potato tubers, but effective chemical control is still lacking. In this study, an attempt was made to control potato common scab by inoculating potatoes with Bacillus velezensis (B. velezensis) and to further investigate the mechanism of biological control. The results showed that B. velezensis Y6 could reduce the disease severity of potato common scab from 49.92 ± 25.74% (inoculated with Streptomyces scabies (S. scabies) only) to 5.56 ±1.89% (inoculated with S. scabies and Y6 on the same day) and increase the potato yield by 37.32% compared with the control under pot experiment in this study. Moreover, in the field trial, it was found that Y6 could also significantly reduce disease severity from 13.20 ± 1.00% to 4.00 ± 0.70% and increase the potato yield from 2.07 ± 0.10 ton/mu to 2.87 ± 0.28 ton/mu (P < 0.01; Tukey's test).Furthermore, RNA-seq analysis indicated that 256 potato genes were upregulated and 183 potato genes were downregulated in response to B. velezensis Y6 inoculation. In addition, strain Y6 was found to induce the expression of plant growth-related genes in potato, including cell wall organization, biogenesis, brassinosteroid biosynthesis, and plant hormone transduction genes, by 1.01-4.29 times. As well as up-regulate hydroquinone metabolism-related genes and several transcription factors (bHLH, MYB, and NAC) by 1.13-4.21 times. In summary, our study will help to understand the molecular mechanism of biological control of potato common scab and improve potato yield.